State Anhedonia in Young Healthy Adults: Psychometric Properties of the German Dimensional Anhedonia Rating Scale (DARS) and Effects of the COVID-19 Pandemic - Wellan, Sarah A.; Daniels, Anna; Walter, Henrik (Frontiers in Psychology, 2021)
Healthy reward processing is a complex interplay of several components. Recent self-report measures of anhedonia, the decrease or loss of hedonic capacity, take this complexity into account. The Dimensional Anhedonia Rating Scale (DARS) measures interest, motivation, effort and consummatory pleasure across four domains: hobbies, food/drink, social activities and sensory experiences. In the present cross-sectional survey study, we validated the German version of the DARS in a sample of 557 young healthy adults. Factor structure as well as convergent and divergent validity were assessed. As a secondary aim, we examined the effects of the COVID-19 pandemic on state anhedonia and depression severity. Our results suggest good convergent and divergent validity and high internal consistency of the German DARS. The original differentiation of four factors mapping onto the four domains was confirmed and measurement invariance before and during the COVID-10 pandemic was established. We conclude that the DARS is a valid instrument to comprehensively assess state anhedonia in healthy German samples. Future studies should further assess the utility of the German DARS in clinical contexts. In line with many previous studies, participants during the pandemic reported significantly higher levels of depressive symptoms compared to participants in the months before. We found no indication that the COVID-19 pandemic affected state hedonic capacity.